The lysosomal trafficking regulator is necessary for normal wound healing. Issue 1 (27th November 2021) - Zbinden, Jacob C.; Mirhaidari, Gabriel J. M.; Blum, Kevin M.; Musgrave, Andrew J.; Reinhardt, James W.; Breuer, Christopher K.; Barker, Jenny C.
Abstract: Non‐healing wounds are a major threat to public health throughout the United States. Tissue healing is complex multifactorial process that requires synchronicity of several cell types. Endolysosomal trafficking, which contributes to various cell functions from protein degradation to plasma membrane repair, is an understudied process in the context of wound healing. The lysosomal trafficking regulator protein (LYST) is an essential protein of the endolysosomal system through an indeterminate mechanism. In this study, we examine the impact of impaired LYST function both in vitro with primary LYST mutant fibroblasts as well as in vivo with an excisional wound model. The wound model shows that LYST mutant mice have impaired wound healing in the form of delayed epithelialization and collagen deposition, independent of macrophage infiltration and polarisation. We show that LYST mutation confers a deficit in MCP‐1, IGF‐1, and IGFBP‐2 secretion in beige fibroblasts, which are critical factors in normal wound healing. Identifying the mechanism of LYST function is important for understanding normal wound biology, which may facilitate the development of strategies to address problem wound healing.